Non-Occupational HIV Post-exposure Prophylaxis: A 10-Year Retrospective Review of Data Following Sexual Exposure From Yaounde Central Hospital, Cameroon - Charles Kouanfack, MD, PhD; Hermine Meli, MD; Samuel N. Cumber, MPH, PhD; Fala Bede, MD, MPH; Claude N. Nkfusai, MSc; Patience Y. Ijang, MSc; Emerson Wepngong, MD; Olga Yvonne M. Bassong, MPH, PhD; Benjamin-Alexandre Nkoum, MPH, PhD (Global Health and Education Projects, Inc., 2019)
Background: Human Immunodeficiency Virus (HIV) post exposure prophylaxis (PEP) consists of administering antiretroviral therapy within 72 hours of viral exposure and continued for four weeks. PEP has been shown to be an important means of preventing and decreasing the number of new HIV infections in the general population. The purpose of this study was to describe the profile of patients who consulted at the HIV/AIDS Care and Treatment Center of the Yaounde Central Hospital (YCH) for PEP following non-occupational exposure to HIV. To attain our objective, we carried out a 10-year retrospective review of patient records of all persons who consulted for accidental HIV exposure at the YCH, Cameroon. Methods: This study was an observational, retrospective analysis of hospital records of persons who consulted for PEP following accidental exposure to HIV in the outpatient HIV clinic at YCH between January 2007 and December 2016. Data extracted from patients' records were: type of HIV exposure, sex, age, profession, level of education, HIV status of source and time to consultation. Descriptive and inferential statistics were analyzed using STATA IC 12.0. Results were presented as median and interquartile range for continuous variables. Categorical variables were expressed as frequencies and proportions. Results: There were 628 consultations for PEP of which 48% (299/628) were as a result of nonoccupational post exposure prophylaxis (nPEP). Of those who consulted for HIV PEP following nonoccupational exposure, 78% (234/299) were females; adolescents group (15-19 years) and young adults group (20 - 24yrs.) constituted 41% (125/299). Forty percent (1208/299) were secondary or high school students (level of education) and 88% (262/299) were non-healthcare workers. The median timeto- consultation for non-occupational PEP (nPEP) was 19 hours (IQR: 12.4-25.0) and HIV status of the source was unknown in 64% (191/299) of cases and positive for 8% (25/299) of cases. The most frequent indications for consulting were sexual assault, 75% (224/299); condom slippage or breakage, 10% (30/299); and unprotected consensual sexual intercourse, 15% (45/299). Conclusion and Global Health Implications: Consultations for nPEP are as frequent as those occupational PEP (48% vs 52% in this study) in clinical practice at YCH. A good history of the source is important as it prevents unnecessary prescriptions of ART (which themselves have potential side effects) for persons consulting for potential HIV non-occupational exposure. In our study, we found that 27% (82/299) unnecessary ART prescriptions were avoided by determining that the exposure source person had negative HIV status. In addition, adolescent or young females consulting for nPEP in clinics could be potential victims of sexual assault or gender-based violence. Where possible, we recommend that clinicians consider the source of suspected viral exposure in clinical practice prior to administering ART for PEP. Key words: • Human Immunodeficiency Virus • Yaounde Central Hospital (Hôpital Central Yaoundé) • Post-exposure Prophylaxis • Cameroon • Sexual exposure • Non-occupational Post Exposure Prophylaxis • HIV • PEP • nPEP • AIDS   Copyright © 2019 Kouanfack et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.